Science and classical education in a nonclassical school: a SPN experience - Fryer, CindyJo (Kansas State University, 2024)
This dissertation explores the implementation of classical education in a non-classical charter high school, with a focus on science education using classical methodologies. Employing techniques like copy work, history-based science teaching (HBST), the Socratic method, and the Progymnastmata, astronomy, and chemistry were taught. To identify classroom tensions, dilemmas, and synergies, the scholarly personal narrative (SPN) method was utilized, resulting in three articles based on the collected data. The first article examines the use of classical methods to create an immersive classroom experience, including copy work, HBST, and the Progymnastmata. The second article focuses on the teaching of unit conversions through copy work, gradual release of responsibility, and model recovery. The third and final article explores the use of a document to promote metacognition through peer learning and reflection. Overall, the study demonstrates that classical education can effectively foster a harmonious relationship between students and teachers in the classroom.
Keywords: Classical education; Science education; Metacognition; Peer learning; History-based science teaching; Inquiry based learning